In vitro Micropropagation of Abutilon indicum L. through Leaf Explants (Plant Tissue Culture and Biotechnology, 2010)
The present investigation was conducted to develop a protocol for rapid callus induction and plant regeneration from leaf explant of Abutilon indicum L. Callus induction and plantlet regeneration at various frequencies were observed on MS using different concentrations of 2,4-D alone or in combination with BAP and Kn. The highest percentage of callus induction was observed with 2.5 mg/l 2,4-D (90) and with combination of 0.5 mg/l Kn (85). Optimum shoot formation was observed on same medium but supplemented with 2.0 mg/l Kn and 1.0 mg/l NAA (11.2). Rooting experiments with half strength of MS revealed that NAA was more suitable for root induction compared to IBA and IAA. The healthy in vitro rooting plantlets were successfully transferred to the field. The survival of the plantlets under ex vitro condition was 87%. Key words: Abutilon indicum, Callus induction, Leaf explants, Micropropagation D.O.I. 10.3329/ptcb.v19i2.5435 Plant Tissue Cult. & Biotech. 19(2): 177-184, 2009 (December)